High bandwidth zero voltage injection method for sensorless control of PMSM - Xie, G.; Lu, K.; Dwivedi, Sanjeet Kumar; Riber, R. (2014)
Abstract: High frequency signal injection is widely used in PMSM sensorless control system for low speed operations. The conventional voltage injection method often needs filters to obtain particular harmonic component in order to estimate the rotor position; or it requires several voltage pulses to be injected before the position may be estimated. In this paper, a single pulse zero voltage injection method is proposed. The rotor position is directly estimated from the current ripple at half of the switching frequency. No machine parameters are needed and using of filters is avoided. This results in a fast current regulation performance. Injection of zero voltage also minimizes the inverter voltage error effects caused by the dead-time.